2022
DOI: 10.1088/1757-899x/1220/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Crash testing and evaluation of W-beam guardrail using finite elements method

Abstract: On public roads, the guardrails represent the most used passive protection devices in the case of road accidents. Their role is to absorb the car impact energy. This paper presents and analyses tests of a W-beam guardrail type placed on the roadside using the finite element method. The introduction of the paper presents the state of the art, the requirements and the standards used for guardrails testing and crash test methods. In the second part of the paper is achieved the CAD model of the parapet and the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Matej et al [19] presented a steel-reinforced wooden W-beam guardrail design tested according to the EN1317 standard. Many researchers [20][21][22][23] provided an overview of the behavior of crashworthiness of roadside W-beam guardrail with different designs. Ferdous et al [24] performed simulations with variable guardrail vehicle impact heights with Wbeam guardrail.…”
Section: Figure 1 W-beam Guardrail [8]mentioning
confidence: 99%
“…Matej et al [19] presented a steel-reinforced wooden W-beam guardrail design tested according to the EN1317 standard. Many researchers [20][21][22][23] provided an overview of the behavior of crashworthiness of roadside W-beam guardrail with different designs. Ferdous et al [24] performed simulations with variable guardrail vehicle impact heights with Wbeam guardrail.…”
Section: Figure 1 W-beam Guardrail [8]mentioning
confidence: 99%
“…A new method for testing dispersion devices used for pesticide application in crops or orchards and not only has been discovered and was highly debated by other researchers with the same thoughts and aims to make an efficiency in pesticide management. Early researches in pesticide drift monitoring were also made using image analysis technique and LIDAR sensors (Gheres, et al, 2023;Li, et al, 2023;Kashdan, et al, 2007;Gregorio, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This flexibility allows for an unlimited number of analyses using FE, facilitating the exploration of various parameters and variables. Numerous studies have investigated the crash performance of road safety systems by creating FE models (Langseth et al, 1999;Pawlak, 2016;Yücel et al, 2018;Gheres & Scurtu, 2022;Wolny et al, 2022). Comparisons between real crash tests and FE models have indicated that the computational models well represent actual conditions.…”
Section: Introductionmentioning
confidence: 99%